2018
DOI: 10.1021/acs.joc.8b02553
|View full text |Cite
|
Sign up to set email alerts
|

Total Solid-Phase Synthesis of Dehydroxy Fengycin Derivatives

Abstract: A rapid and efficient solid-phase strategy for the synthesis of dehydroxy fengycins derivatives is described. This synthetic approach involved the linkage of a Tyr to a Wang resin via a Mitsunobu reaction and the elongation of the peptide sequence followed by subsequent acylation of the N-terminus of the resulting linear peptidyl resin, esterification of the phenol group of a Tyr with an Ile, and final macrolactamization. The amino acid composition as well as the presence of the N-terminal acyl group significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Similar or improved results were obtained when this methodology was employed to prepare 17B – 17D , where we replaced the initial d -Thr residue at position 4 by the fengycin A naturally occurring d -allo-Thr and also their corresponding enantiomers (Figure C). Previous reports have shown that the chirality of the residues within the cyclic core of natural fengycin affects the ease of ring formation. , However, our results in the synthesis of analogues 17B and 17D , using l -amino acids, show that this is not the case for fengycin lactam derivatives, as all of them could be synthesized with similar overall efficacy (50–70% crude purities, Figure C and Figures S23–29). Overall, the synthesis of 17A – D clearly demonstrates the suitability of our synthetic approach for the convenient SPPS of fengycin cyclic lipopeptide amide analogues.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Similar or improved results were obtained when this methodology was employed to prepare 17B – 17D , where we replaced the initial d -Thr residue at position 4 by the fengycin A naturally occurring d -allo-Thr and also their corresponding enantiomers (Figure C). Previous reports have shown that the chirality of the residues within the cyclic core of natural fengycin affects the ease of ring formation. , However, our results in the synthesis of analogues 17B and 17D , using l -amino acids, show that this is not the case for fengycin lactam derivatives, as all of them could be synthesized with similar overall efficacy (50–70% crude purities, Figure C and Figures S23–29). Overall, the synthesis of 17A – D clearly demonstrates the suitability of our synthetic approach for the convenient SPPS of fengycin cyclic lipopeptide amide analogues.…”
mentioning
confidence: 99%
“… 24 , 25 This is clearly highlighted by the fact that to date no synthetic strategy has succeeded in delivering a completely natural fengycin peptide and, only very recently, a solid phase peptide synthesis (SPPS) approach which enabled the synthesis of several fengycin analogues was reported. 26 While this marked a significant advance for the field, the reported approach only afforded modest product yields and it did not address the issue of the fengycin peptides’ innate instability.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Their syntheses are a challenge due to the inherent lability of the phenyl ester bond, which should be formed during the last steps of the synthetic strategy. Feliu and Planas' group developed an elegant strategy (Rosés et al, 2016;Roses et al, 2018), based on the following: incorporation of the first amino acid through the side-chain with the carboxylic acid protected in the form of the allyl ester; elongation of the peptide chain; formation of the phenyl ester with an N-Alloc-amino acid; treatment with Pd(0) to remove the allyl and the Alloc protecting groups; onresin cyclization; and global deprotection and cleavage from the resin.…”
Section: Introductionmentioning
confidence: 99%